2012
DOI: 10.1099/vir.0.034405-0
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus Rta-mediated transactivation of p21 and 14-3-3σ arrests cells at the G1/S transition by reducing cyclin E/CDK2 activity

Abstract: Many herpesviral immediate-early proteins promote their robust lytic phase replications by hijacking the cell cycle machinery. Previously, lytic replication of Epstein-Barr virus (EBV) was found to be concurrent with host cell cycle arrest. In this study, we showed that ectopic expression of EBV immediate-early protein Rta in HEp-2 cells resulted in increased G1/S population, hypophosphorylation of pRb and decreased incorporation of 5-bromo-29-deoxyuridine. In addition, EBV Rta transcriptionally upregulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Our finding that K-Rta arrests cells in G 0 /G 1 phase is in general agreement with recent studies that investigated the role of EBVencoded Rta (E-Rta) in cell cycle regulation (18). The expression of inducible E-Rta in 293 and nasopharyngeal carcinoma (NPC)-derived cells resulted in G 1 arrest (18,19), which was associated with elevated levels of p21 and p27.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that K-Rta arrests cells in G 0 /G 1 phase is in general agreement with recent studies that investigated the role of EBVencoded Rta (E-Rta) in cell cycle regulation (18). The expression of inducible E-Rta in 293 and nasopharyngeal carcinoma (NPC)-derived cells resulted in G 1 arrest (18,19), which was associated with elevated levels of p21 and p27.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of inducible E-Rta in 293 and nasopharyngeal carcinoma (NPC)-derived cells resulted in G 1 arrest (18,19), which was associated with elevated levels of p21 and p27. However, we did not notice any significant changes in the expression of p21 in K-Rta-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, knockdown of endogenous Sp1 expression suppressed lytic EBV reactivation ( Fig. 4C and D), supporting its role in lytic reactivation of EBV (49,(60)(61)(62)(63). Furthermore, Sp1 localized at replication compartments during lytic reactivation (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In order to validate that EBV Rta does bind to these cellular promoters, chromatin immunoprecipitation (ChIP) assay was performed using specific antibodies against EBV Rta and normal rabbit IgG, which served as a control to estimate nonspecific binding signals. In addition, the promoter region of SFN, which is known to be positively regulated upon Rta binding (12), served as a positive control. The results indicated that EBV Rta bound to the promoter regions of MYC, CCND1, JUN, and SFN at an early time point (12 h) after Dox treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%